Functional analysis of conserved sequences within a temporally restricted neural precursor cell enhancer. - Kuzin, A.; Kundu, M.; Brody, T.; Odenwald, W.F. (Mechanisms of Development, 2011)
Many of the key regulators of Drosophila CNS neural identity are expressed in defined temporal orders during neuroblast (NB) lineage development. To begin to understand the structural and functional complexity of enhancers that regulate ordered NB gene expression programs, we have undertaken the mutational analysis of the temporally restricted nerfin-1 NB enhancer. Our previous studies have localized the enhancer to a region just proximal to the nerfin-1 transcription start site. Analysis of this enhancer, using the phylogenetic footprint program EvoPrinter, reveals the presence of multiple sequence blocks that are conserved among drosophilids. cis-Decoder alignments of these conserved sequence blocks (CSBs) has identified shorter elements that are conserved in other Drosophila NB enhancers. Mutagenesis of the enhancer reveals that although each CSB is required for wild-type expression, neither position nor orientation of the CSBs within the enhancer is crucial for enhancer function; removal of less-conserved or non-conserved sequences flanking CSB clusters also does not significantly alter enhancer activity. While all three conserved E-box transcription factor (TF) binding sites (CAGCTG) are required for full function, adding an additional site at different locations within non-conserved sequences interferes with enhancer activity. Of particular note, none of the mutations resulted in ectopic reporter expression outside of the early NB expression window, suggesting that the temporally restricted pattern is defined by transcriptional activators and not by direct DNA binding repressors. Our work also points to an unexpectedly large number of TFs required for optimal enhancer function - mutant TF analysis has identified at least four that are required for full enhancer regulation.